2012
DOI: 10.7555/jbr.26.20110054
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin, sitagliptin and metformin, or sitagliptin and amitriptyline attenuate streptozotocin-nicotinamide induced diabetic neuropathy in rats

Abstract: Diabetic neuropathies are a family of nerve disorders caused by diabetes. Symptoms of the disease include nerve palsy, mononeuropathy, mononeuropathy multiplex, diabetic amyotrophy, painful polyneuropathy, autonomic neuropathy, and thoracoabdominal neuropathy. In this study, type 2 diabetes in rats was induced with nicotinamide-streptozotocin. Drug treatment was initiated on the d 15, with the combination regimen of metformin, pioglitazone and glimipiride or metformin and sitagliptin or sitagliptin, amitriptyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
(29 reference statements)
2
23
1
Order By: Relevance
“…This could be due to dehydration, increase in muscle wasting (56) and catabolism of fats and proteins (57). These results run parallel with the studies of Pierre et al, (47) and Sharma et al, (58). Oral administration of gallic acid and p-coumaric acid to diabetic rats improved body weight and this could be due to a better control of hyperglycemic state in the diabetic rats.…”
Section: Discussionsupporting
confidence: 81%
“…This could be due to dehydration, increase in muscle wasting (56) and catabolism of fats and proteins (57). These results run parallel with the studies of Pierre et al, (47) and Sharma et al, (58). Oral administration of gallic acid and p-coumaric acid to diabetic rats improved body weight and this could be due to a better control of hyperglycemic state in the diabetic rats.…”
Section: Discussionsupporting
confidence: 81%
“…Conversely, it is suggested that there are no differences in body weight between healthy and diabetic rats at the end of third week after birth [5]. It is reported that sitagliptin did not change the body weights of different species of diabetic animals [31,32]. By contrast with the previous studies, administration of sitagliptin regulated the body weight of diabetic rats in this study.…”
Section: Discussioncontrasting
confidence: 72%
“…This precludes the possibility of its role in the treatment of diabetic neuropathic pain when administrated in acute doses. These results are consistent with a previous study that has reported increased pain sensitivity following sitagliptin administration for 35 days in STZ-nicotinamide-induced diabetic neuropathy in rats [42]. However, another study has reported that administration of sitagliptin for 48 weeks significantly reversed the decrease in tail-flick latencies in STZ-induced diabetic animals [43].…”
Section: Discussionsupporting
confidence: 93%